A game for the living - Highsmith, Patricia, 1921-1995
Ramón mends furniture.Theodore paints. A devout Catholic, Ramón lives in Mexico City, not far from where he was born into poverty.Theodore, a rich German transplanted to a country where money buys some comfort but no peace, believes in nothing at all.You'd think the two had nothing in common. Except, of course, that both had slept with Lelia.The two were good friends, so neither minded sharing her affections.They did mind, however, when Lelia was found raped, murdered, and horribly mutilated.The two friends, suspects both, twist in a limbo of tension and doubt, each seeking his own form of solace and truth.